Hijacking Sorrow, Joy, Pleasure and Reward: A Philosophical Interpretive Framework for the Theory of Alcohol Addiction - Valery Yevarouski (Sociologija: Mintis ir Veiksmas, 2018)
[full article, abstract in English; only abstract in Lithuanian]